2019
DOI: 10.1111/mms.12602
|View full text |Cite
|
Sign up to set email alerts
|

Passive acoustic monitoring predicts daily variation in North Atlantic right whale presence and relative abundance in Roseway Basin, Canada

Abstract: North Atlantic right whale monitoring in Roseway Basin, Canada, is primarily based on short‐term (<14 d) visual surveys conducted during August–September. Variability in survey effort has been the biggest limiting factor to studying changes in the population's occurrence and habitat use. Such efforts could be enhanced considerably using passive acoustic monitoring (PAM). We sought to determine if variation in whale presence, relative abundance, demography, and/or behavior (estimated through visual surveys) cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…As we have shown, right whale calling is ephemeral, highly variable, and dependent on behavioral state rather than the number of observed individuals. Our results align with those of Clark et al (2010) but contrast with findings from Matthews et al (2001) and Durette-Morin et al (2019), both of which reported a statistically significant predictive relationship between the numbers of calls and the numbers of whales observed. The discrepancy may be attributed to the aggregation sizes considered, where 89% (33 of 37) of our observations were associated with observations with more than 10 whales compared to 14% (3 of 12) and 22% (5 of 23) from Matthews et al (2001) and Durette-Morin et al (2019), respectively.…”
Section: Characterizing Whale Countsupporting
confidence: 73%
See 3 more Smart Citations
“…As we have shown, right whale calling is ephemeral, highly variable, and dependent on behavioral state rather than the number of observed individuals. Our results align with those of Clark et al (2010) but contrast with findings from Matthews et al (2001) and Durette-Morin et al (2019), both of which reported a statistically significant predictive relationship between the numbers of calls and the numbers of whales observed. The discrepancy may be attributed to the aggregation sizes considered, where 89% (33 of 37) of our observations were associated with observations with more than 10 whales compared to 14% (3 of 12) and 22% (5 of 23) from Matthews et al (2001) and Durette-Morin et al (2019), respectively.…”
Section: Characterizing Whale Countsupporting
confidence: 73%
“…Furthermore, Durette-Morin et al ( 2019) used fixed moorings that monitor constantly (24 h d −1 , as opposed to 0.5 to 6 h d −1 when weather is good) regardless of the number of whales present. Our study also occurred in a different habitat and time of year from the previously mentioned papers, as Clark et al (2010) studied Cape Cod Bay from January to May, Durette-Morin et al (2019) studied Roseway Basin from August to September, and Matthews et al (2001) studied the Great South Channel and Cape Cod from April to May and the Bay of Fundy from August to September. Thus, habitat and time of year may affect whale behavior and contribute to the observed differences among these studies.…”
Section: Characterizing Whale Countmentioning
confidence: 91%
See 2 more Smart Citations
“…One of PAM's most common applications is in marine mammal monitoring and conservation. Marine mammals produce complex vocalizations that are species-specific (if not individually unique), and such vocalizations can be used when estimating species' distributions and habitat use (Durette-Morin et al, 2019;Kowarski & Moors-Murphy, 2020). PAM applications in marine mammal research span from the study of their vocalizations and behaviours (Madhusudhana et al, 2019;Vester et al, 2017) to assessing anthropogenic disturbance (Nguyen Hong Duc et al, 2021).…”
Section: Introductionmentioning
confidence: 99%